Evaluation of the influence of blood glucose level on oral candidal colonization in complete denture wearers with Type-II Diabetes Mellitus: An in vivo Study - Dhanraj Muthuveera Ganapathy; Sajeesh Joseph; Padma Ariga; Anand Selvaraj (Dental Research Journal, 2013)
Background: Candidal colonization in complete denture wearers is a commonly encountered condition that worsens in the presence of untreated Diabetes Mellitus. The aim of this study was to evaluate the correlation between oral candidiasis in denture-bearing mucosa and elevated blood glucose levels in complete denture wearers and to evaluate the effect of oral hypoglycemic drug therapy in controlling oral candidal colonization in denture-bearing mucosa of complete denture wearers with Type II Diabetes Mellitus. Materials and Methods: This prospective observational study involved the participation of 15 complete denture wearers with Type II Diabetes Mellitus. The sample collection was made prior and after oral hypoglycaemic drug intervention, by swabbing the rugal surfaces of palatal mucosa, cultured and the density of the candidal colony formed was analyzed and interpreted as colony forming units (CFU) per mL. The candidal samples CFU and corresponding pre- and post-prandial blood glucose levels were estimated, analyzed and compared using Karl Pearson correlation analysis and paired t-test (α = 0.05). Results: The Karl Pearson correlation analysis showed that there was a positive correlation between the blood glucose levels (PPS and FBS) and the candidal colonization (CFU) ( P < 0.05). The mean values of all the variables were analyzed using the paired t-test. There was significant reduction in the mean values of blood glucose levels ( P < 0.001) and the mean values of the CFU ( P < 0.001) following oral hypoglycemic drug therapy. Conclusion: Positive correlation was observed between oral candidiasis in complete denture-bearing mucosa and elevated blood glucose levels and oral hypoglycemic drug therapy has a positive effect in controlling oral candidal colonization in complete denture wearers with Type II Diabetes Mellitus.